TOTAL QUALITY MANAGEMENT UNTUK PENDIDIKAN MENUJU N-GENERATION - Hastuti, Setyo (STIE YPPI Rembang, 2008)
Science develops fast nowadays. The unlimited informa- tion make someone able to create new things. But informa- tion also have negative effect, because it can make some- one get difficulty to make decisions. So, developing of creativities are needed in information era. This attitudes can be found in n-agent, it is the attitude to choose suitable infor- mation , spreadÂ informationÂ in net working to create new ideas.Â The ability to create new things from the existence of the information has to be developed in Educational System. So, the new generation will bore. The n-generation needs teacherâs corps that has high qualities and masters digital language.Key Words: Education, N-Generation.